2008
DOI: 10.1016/j.jtcvs.2008.03.067
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of right ventricle to coronary artery connections in infants with pulmonary atresia and intact ventricular septum

Abstract: The location and ligation of right ventricle to coronary artery connections can be reliably accomplished off bypass. Coronary flow became antegrade, improving myocardial oxygenation. No myocardial damage was observed. Inapparent right ventricle to coronary artery connections occasionally enlarge secondarily after right ventricular decompression, making early follow-up evaluation necessary after ligation. Despite the initial presence of significant right ventricle to coronary artery connections, 2-ventricle rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 25 publications
(74 reference statements)
2
33
0
Order By: Relevance
“…Normal epicardial antegrade coronary arterial flow could be restored and/or augmented by abolishment of right ventricle stroke volume. Our findings are in agreement with the findings of a surgical ligation series of right ventricle to coronary artery connections: it showed that myocardial oxygenation improved as antegrade coronary artery perfusion was restored . Furthermore, similar to our experience during follow‐up, the effect seemed to persist over time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Normal epicardial antegrade coronary arterial flow could be restored and/or augmented by abolishment of right ventricle stroke volume. Our findings are in agreement with the findings of a surgical ligation series of right ventricle to coronary artery connections: it showed that myocardial oxygenation improved as antegrade coronary artery perfusion was restored . Furthermore, similar to our experience during follow‐up, the effect seemed to persist over time.…”
Section: Discussionsupporting
confidence: 91%
“…In patients with coronary artery stenosis or RVDCC to the left ventricular myocardium, decompression of the right ventricle may involve myocardial infarction with fatal outcome—special care should be taken during surgery to maintain coronary perfusion . Limited treatment options with varying degrees of success have been reported for this subgroup and consist of right ventricle plication, tricuspid valve narrowing or closure, or ligation of ventriculo‐coronary connections; when the LV is significantly compromised, cardiac transplant may be the only option …”
Section: Discussionmentioning
confidence: 99%
“…Few other studies have focused on the long‐term implications of ventriculocoronary connections although a study by Dyamenahalli and colleagues reviewed a cohort of 210 patients with pulmonary atresia with intact ventricular septum and found that those with greater severity of coronary anomalies were more likely to develop left ventricular dysfunction . Furthermore, Foker and colleagues reported a small series of patients in which surgical ligation of ventriculocoronary connections was conducted at the time of biventricular repair and noted that ligation of such connections improved myocardial oxygenation, demonstrating the mechanism of myocardial damage secondary to such ventriculocoronary connections . Guleserian and colleagues reviewed the outcomes of a series of patients who had pulmonary atresia with intact ventricular septum they deemed to have right ventricle‐dependent coronary circulation who underwent functionally univentricular palliation.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 Coronary artery abnormalities occur in 30%-60% of patients with PA-IVS. 7,28,33,34 In some cases, fi stulous connections between the RV cavity and coronary sinusoids form multiple small communications into branches of coronary arteries. The coronary artery anatomy is classifi ed as (1) a fi stula alone or (2) a fi stula plus stenoses or interruptions to the coronary arteries.…”
Section: Morphologymentioning
confidence: 99%
“…Although major RV-coronary arterial fi stulas can be detected by echocardiography, their detailed courses, numbers, and sizes can be determined only by cineangiography. 4,9,33 …”
Section: Morphologymentioning
confidence: 99%